Cutaneous Rhinosporidiosis - Kunar Mandal Sanjay; Dutta Sanjib; Roy Shravasti (Wolters Kluwer Medknow Publications, 2000)
A case of rhinosporidiosis with rare cutaneous affection along with its histopathological features is being described.